Optimalisasi Pendekatan MIKiR Sebagai Solusi Pembelajaran Abad 21 Bagi Guru SD Muhammadiyah Kota Medan - Eko Febri Syahputra Siregar; Suci Perwita Sari (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2020)
The study aims to answer the learning challenges on the 21st century. Teachers are required to improve their abilities, especially in managing student-oriented learning. Teacher creativity is the basis for designing meaningful learning. Participants of this activity were teachers of SD Muhammadiyah 29 Sei Mencirim and SD Muhammadiyah 38 Medan Krio. The target of this activity is that teachers are able to design active learning scenarios that can be applied in class. The methods for implementing this activity are: 1) Initial meeting with school principals, 2) Training activities, 3) Evaluation, and 4) Follow-up plans. Based on the results of the activity, the teachers have been able to design active learning scenarios and 21st century skills. The implementer hopes that participants will familiarize themselves with implementing the results of activities in supporting the learning being carried out and can pass them on to other teachers.